2015
DOI: 10.1007/s00402-015-2172-3
|View full text |Cite
|
Sign up to set email alerts
|

Can larger-bodied cemented femoral components reduce periprosthetic fractures? A biomechanical study

Abstract: The use of large body polished tapered cemented stems for neck of femur fractures increases the torque to failure in a biomechanical model and therefore is likely to reduce late periprosthetic fracture risk in this vulnerable cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“… 2014 , Ginsel et al. 2015 ). These suggestions remain to be investigated further regarding specific stems.…”
Section: Discussionmentioning
confidence: 99%
“… 2014 , Ginsel et al. 2015 ). These suggestions remain to be investigated further regarding specific stems.…”
Section: Discussionmentioning
confidence: 99%
“…No studies, to our knowledge, have compared the TS and CB principles. One study by Ginsel et al 54 compared TS-designed Exeter stems with identical length and offset, but with different cross-section size (202), and found large stems to be more resistant to torque forces for fracture. The wedge polished TS design facilitates a thicker cement mantle around the tip of the stem than the straight and anatomic CB-designed stems.…”
Section: Mechanical Studies Comparing the Taper-slip And Composite-bementioning
confidence: 99%
“…Mechanically, it has been shown that larger stems can improve primary stability of both cemented (Ginsel et al. 2015) and cementless (Fottner et al. 2017) stems due to a better bone load.…”
Section: Discussionmentioning
confidence: 99%
“…Ginsel et al. (2015) found that an Exeter stem (Stryker Orthopaedics, Mahwah, NJ, USA) with a larger cross-section tolerates more torque until failure, Morishima et al. (2014) found that an Exeter stem (Stryker) with increased length tolerates more torque and energy until failure.…”
mentioning
confidence: 99%